NDRG2 inhibition facilitates angiogenesis of hepatocellular carcinoma - Wang Jianlong (De Gruyter, 2021)
Hepatocellular carcinoma (HCC) is an angiogenesis-dependent tumor, and angiogenesis plays pivotal roles in progression and hematogenous metastasis. Upregulating NDRG2 expression could inhibit endothelial cell proliferation and tumor angiogenesis. However, the development of angiogenesis is a complicated and dynamic process, and the specific mechanisms that NDRG2 influences its progression are largely unknown. Conditioned media (CM) was collected from HCC cells. Cell viability, migration assay, tube formation, and western blot were used to evaluate the effect of NDRG2 on angiogenesis in HCC cells. ELISA assay was used to measure the level of VEGFA in CM. CM from NDRG2 knockdown cells significantly promoted HUVECs proliferation, migration, and tube formation compared with control cells. The level of VEGFA in CM was increased by NDRG2 knockdown relative to the control group. The expression of VEGFA, HIF-1α, and p-Akt was significantly increased in NDRG2 knockdown cells. CM from NDRG2 knockdown cells with VEGFA antibody failed to induce HUVEC proliferation, migration, and tube formation. YC-1 significantly inhibited the level of VEGFA in CM from NDRG2 knockdown cells. YC-1 also inhibited the expression of VEGFA and HIF-1α. Therefore, NDRG2 inhibition promoted the angiogenesis of HCC via VEGFA and may be used to be an anti-angiogenesis target.